Science and Mathematics Education in Schools: A Systematic Literature Review (SLR) Based on International Studies - Tanawin Kaliang (SABIQ: Jurnal Sosial dan Bidang Pendidikan, 2025)
Science and mathematics education plays a strategic role in forming the foundation of intellectual competence and 21st-century skills that increasingly demand high scientific literacy and numeracy. The transformation of global society towards a digital economy, artificial intelligence, and environmental sustainability also drives the urgency of improving the quality of science and mathematics education from the elementary education level. This study uses the Systematic Literature Review method based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. The results of this study are: 1) Science and mathematics education in schools is undergoing a global transformation towards a more active, contextual, and technology-based approach; and 2) Countries need to strengthen teacher training systems in STEM pedagogy, curricula must be flexible to respond to local and global challenges, and cross-cultural and longitudinal research is needed on the impact of innovative learning.